METHODOLOGY OF WORKING ON ARTISTIC TEXT IN 3-4 GRADES (TAMADDUN NURI JURNALI, 2024)
The article discusses how to shape the knowledge of elementary school students on the basis of literary texts and teach them to speak fluently, and at the same time educate them in the spirit of patriotism and how to form them.